Agricultural Diversification as a Strategy for Household Economic Resilience Among Farmers - Kamakaula, Yohanes (West Science Agro, 2025)
This study examines agricultural diversification as a strategy for strengthening household economic resilience among smallholder farmers. Using a qualitative approach, in-depth interviews were conducted with five farmer informants who engaged in multiple agricultural activities, including cultivating food crops, cash crops, and livestock rearing. The findings reveal that diversification reduces dependence on a single commodity, mitigates risks from price fluctuations and crop failures, and enhances household food security. Farmers also emphasized that diversification fosters adaptive capacity by encouraging experimentation with new crops and farming practices. However, challenges such as limited access to capital, weak market linkages, and inadequate extension services hinder the effectiveness of diversification. Overall, the study highlights that agricultural diversification serves as both a survival mechanism and a resilience-building strategy for rural households. Policy support in the form of credit access, market development, and technical assistance is essential to optimize the benefits of diversification and promote sustainable rural livelihoods.